PENGARUH KOMITE AUDIT, DEWAN DIREKSI DAN PROFITABILITAS TERHADAP PUBLIKASI SUSTAINABILITY REPORT STUDI KASUS PADA PERUSAHAAN TAMBANG YANG TERDAFTAR PADA BEI (PERIODE 2010-2015) - Dika Candra Laili; Fitria Ayu Islamiyah; Tri Ratnawati (Universitas Prof.Hazairin,SH Bengkulu, 2024)
Growth has become a demanding goal for most companies. In addition, growth is always included in considering a company's performance to calculate company value. If a company experiences too high financial growth and funding from debt, the company could be at risk of experiencing liquidity and solvency problems. However, if the company experiences financial growth that is too low, the company may also be at risk of bankruptcy because it cannot optimize the use of its resources. This is where the role of the Sustainable Growth Rate (SGR) lies, which can help companies identify their growth problems. This research uses mining sector companies as research objects. The aim of the research is to find the influence of the audit committee, direction board and profitability towards the publication of sustainability reports. The method used for analysis is descriptive. For the results. The Audit Committee and Board of Directors have influence on the disclosure of Sustainability Reports in mining companies. Meanwhile, the Profitability variable has no influence on the disclosure of Sustainability Reports in mining sector companies listed on the IDX for the period 2010 to 2015.